2014
DOI: 10.1007/s11356-014-4017-y
|View full text |Cite
|
Sign up to set email alerts
|

Cultivar variations in cadmium and lead accumulation and distribution among 30 wheat (Triticum aestivum L.) cultivars

Abstract: In recent years, heavy metal pollution in agricultural soil in China has received public concern. The concept of low-accumulation cultivars (LACs) was proposed to minimize the influx of pollutants to the human food chain. Variations in Cd and Pb accumulation, distribution, and tolerance among 30 wheat (Triticum aestivum L.) cultivars were studied in a hydroponic experiment to preliminary identify LACs of Cd or Pb for further field experiments. Of the 30 wheat cultivars tested, 27 and 26 wheat cultivars showed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
18
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 55 publications
(20 citation statements)
references
References 50 publications
2
18
0
Order By: Relevance
“…Liu et al [13] found that the edible parts of Lvxing 70 and Dongchu have the lowest and highest Cd accumulation properties in the 12 cabbage genotypes, respectively. Liu et al [15] have also confirmed that wheat cultivar LF-13 showed the lowest Cd and Pb accumulation characteristics in their shoots among 30 wheat cultivars. Meanwhile, vegetables are a crop that is accumulated to nitrates easily, which may be related to their nutritional properties [22].…”
mentioning
confidence: 83%
See 3 more Smart Citations
“…Liu et al [13] found that the edible parts of Lvxing 70 and Dongchu have the lowest and highest Cd accumulation properties in the 12 cabbage genotypes, respectively. Liu et al [15] have also confirmed that wheat cultivar LF-13 showed the lowest Cd and Pb accumulation characteristics in their shoots among 30 wheat cultivars. Meanwhile, vegetables are a crop that is accumulated to nitrates easily, which may be related to their nutritional properties [22].…”
mentioning
confidence: 83%
“…These results indicated that hot pepper cultivars, especially the six cultivars (Nos. 1, 3, 4, 5, 7 and 9), have a higher tolerance to Cd and Pb contamination in agricultural soils compared with other crop cultivars, such as pakchoi (Brassica chinensis L.) [28], wheat (Triticum aestivum L.) [15] and tomato (Solanum lycopersicum L.) [10]. The stimulatory effect of heavy metals on plant growth may be a case of hormesis due to the physiological toxicity of heavy metals ion [29,30].…”
Section: Fruit Biomassmentioning
confidence: 99%
See 2 more Smart Citations
“…Therefore, it is imperative to find an instantaneous and effective method to reduce the potential health risks of Cd entering the human food chain through the consumption of pokchoi. Genetic differences in Cd uptake and translocation in food crops have been observed by many published papers, and the variation existed not only among cultivar species and even within the genetypes but also in cultivar parts [17][18][19]. Selecting appropriate cultivars with a high tolerance to Cd-contaminated soil and low Cd accumulation in the edible parts are reasonable to minimize soil-to-crops of Cd and reduce the risks of Cd to human and animal health.…”
mentioning
confidence: 99%